How can we improve response assessments in MDS? Strategies to improve response assessment in MDS treatment paradigms. Issue 4 (December 2022) - Bejar, Rafael
Abstract: Evaluating response to treatment in MDS represents a major challenge due to its associated complexity and heterogeneity. Although response criteria have been proposed by the IWG and revised on several occasions, these criteria have limitations. This review has outlined some refinements that can be used to improve response assessment and to ensure the identification of clinically meaningful endpoints.